Reflections and insights on the Burden of COVID-19 on various facets of medical education, research, and training: An evaluation in the postpandemic era - Apurba Patra; N B Pushpa; Kumar Satish Ravi; Ritika Singla; Rachna Pasi; Shivendra Singh (Wolters Kluwer Medknow Publications, 2022)
Medical education, an integral part of the modern health-care system, had faced the thrust of the outbreak for the last couple of years. Although the immediate impacts were trivial and managed with online pedagogical approach, on a long run, it seems to spill serious repercussions on medical students, teaching faculties, and administration. Different countries are handling with the situation depending on their financial conditions, task force, and resource allocation. Hence, momentarily, it is quite impractical to reach a global consensus regarding what is the best for students and communities in long run. Meanwhile, each country needs to formulate its own regime to continue with high standard medical teaching and training. Obviously, it may solicit time span, prioritization, and empathy to restructure the medical education without disfiguring its original fabric. The unprecedented use of online pedagogy (prerecorded lectures, medical simulations, virtual cadavers, and video conferencing) has transformed medical education drastically. Although these newer teaching-training policies assisted us to continue with the ongoing curriculum, medical placement/clerkship just resumed with necessary precautions. The assessment part needs extra care and vigilance, as any change or incorporation of newer methods of assessment may even worsen the present state of affairs for both the assessor and the student.